Delusions of Development - Carroll, T. author. aut Link
XV, 269 p.
Keywords: Investigates the World Bank's promotion of market-led development in the underdeveloped world and the impact that this promotion has upon citizenship. This book looks at this subject using case studies drawn from Southeast Asia, one of the world's most diverse regions.